Transient global amnesia due to left temporal haemorrhage. Issue 11 (November 1982) - Landi, Gianluca; Giusti, Maria Cristina; Guidotti, Mario
Abstract : In a patient with transient global amnesia, computed tomography demonstrated a left temporal haemorrhage sparing the hippocampal region.